EFFECT OF DIFFERENT THERAPIES ON FERTILITY AND SERUM PROGESTERONE, METABOLITES AND MINERALS PROFILE IN REPEAT BREEDING CROSSBRED COWS - Kumar, Rajesh; Butani, M G; Dhami, A J; Kavani , F S; Shah , R G (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The study was carried out during breeding season on 31 repeat breeding and 8 normal cyclic crossbred cows to evaluate the efficacy of hormonal and antimicrobial drugs in improving fertility and its effect on serum progesterone, metabolites and macro-minerals profile. Among 10, 7 and 7 repeat breeding cows treated with 0.02 mg GnRH i/m just after AI; 500 mg of hydroxy-progesterone caproate i/m on day 4th or 5th post AI, and antibiotics (Cephalexin or ceftriaxone) i/ut 12-24 hrs post-AI, the conception rates in the treatment cycle were 60.00, 28.57 and 28.57%, respectively, as against only 14.28% in untreated control repeat breeders (n=7) and 62.50% in normal cyclic group. The results of GnRH therapy were better (P<0.05) and at par with the normal fertile group. The average serum P4 concentration for GnRH treated cows was significantly higher (P<0.05), and at par with that of normal cyclic group, as compared to progesterone treated and untreated control groups. The overall average P4 concentration of repeat breeders was significantly lower (P<0.05) than that of normal cyclic cows. The circulatory P4 levels at oestrus were identical and low in most of the groups, but were higher and varied significantly at 20-22 days post-AI due to variable number of animals that conceived in each group. None of the treatments influenced the serum protein profile of repeat breeders. In contrast, the serum cholesterol concentration for GnRH and progesterone treated groups were significantly lower than those of control (247.31±26.50 mg/dl) and normal fertile groups. The mean serum calcium content of repeat breeders and normal fertile cows averaged 8.76±0.25 and 9.66±0.27 mg/dl, respectively; phosphorus 8.90±0.21 and 7.35±0.17 mg/dl, and magnesium 3.70 ±0.15 and 4.16±0.15 mEq/L, all of which differed significantly (P<0.05). The serum inorganic phosphorus content was significantly higher (P<0.05) and magnesium content was lower in GnRH and progesterone treated groups than the antibiotics treated, control and normal cyclic cows. The inorganic phosphorus level was significantly higher in conceived than non-conceived group among repeat breeders. In general, the relatively better results in repeat breeders with GnRH (Busereline), at par with normal fertile cows, suggest that ovulatory problem and endocrine imbalance as the major causes of repeat breeding in cows.